2021
DOI: 10.5897/jhf2021.0670
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of selected multipurpose tree species and moisture conservation structures for degraded dryland rehabilitation in Dugda Dawa District, Southern Ethiopia

Abstract: Land degradation affecting the livelihoods of people living in dryland areas, particularly the Sub-Saharan Africa countries like Ethiopia. Degraded land rehabilitation in dryland is a challenging task due to moisture limitation. This study was conducted to evaluate the effects of soil and water conservation structures on growth of planted tree and rehabilitation of indigenous plant species in West Guji Zone, Dugda Dawa District. Four multipurpose tree species (MPTs) namely Faidherbia albida, Melia azedarach, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Micro-moisture conservation structures in general have a significant contribution to plant survival and growth in the study area. This finding is in line with other studies that indicated that seedlings grown on moisture harvesting structures were significantly thicker, taller, and had higher survival rates than those grown on the normal pits (Mamo et al, 2016;Tadele et al, 2018;Gebru et al, 2019;Kelil et al, 2021).…”
Section: Effects Of Soil and Moisture Conservation Structures On Surv...supporting
confidence: 91%
See 1 more Smart Citation
“…Micro-moisture conservation structures in general have a significant contribution to plant survival and growth in the study area. This finding is in line with other studies that indicated that seedlings grown on moisture harvesting structures were significantly thicker, taller, and had higher survival rates than those grown on the normal pits (Mamo et al, 2016;Tadele et al, 2018;Gebru et al, 2019;Kelil et al, 2021).…”
Section: Effects Of Soil and Moisture Conservation Structures On Surv...supporting
confidence: 91%
“…This study showed that moisture conservation structures significantly affected the survival rate and growth of planted tree species. The results agree with different studies which showed the survival rate of different multipurpose tree species seedlings planted using moisture conservation structures were best than tree seedlings planted in normal pits (Mamo et al, 2016;Tadele et al, 2018;Kelil et al, 2021).…”
Section: Effects Of Soil and Moisture Conservation Structures On Surv...supporting
confidence: 91%
“…Different studies showed that low soil nutrients significantly impair the survival of species (Hau & Corlett, 2003; Holl et al, 2000; O'skarsson et al, 2006; Rose et al, 2016; Sloan & Jacobs, 2013; Valdecantos et al, 2006). Kelil et al (2021) also found the survival percentages of Faidherbia albida (Delile) A. Chev., Melia azedarach L., Moringa stenopetala (Baker f.) Cufod., and Sesbania sesban (L.) Merr.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, the survival rate of Faidherbia albida (F. albida), Melia azedarach (M. azedarach), Moringa stenopetala (M. stenopetala), and S. sesban species has declined over the past five years in the case of Dugda Dawa District, southern Ethiopia. The better survival rate of these species is reported under soil-level bunds and half moons, while all these species planted under normal pits died after four years (Siraj et al, 2021). Since trees and shrubs, which are used to restore the badlands, did not or poorly survive in the dry season in the subhumid tropics (Talema et al, 2019).…”
Section: Factors Affecting the Early Survival Of Tree Seedlings In Re...mentioning
confidence: 96%
“…Research done by Bayen et al (2020), indicates that Senegalia species are suitable for planting in degraded land in semiarid areas in half-moon because the soil moisture content significantly increased from the top to the bottom than in standard plantations and zaı¨ in the case of Burkina Faso. According to Siraj et al (2021), half-moon and soil-level bund in-situ water harvesting structures are also specified as a potential approach for alternative forest and soil restoration in arid areas of Ethiopia. From a slope perspective, Demisachew et al (2018), states that almost all in-situ structures play a crucial role on flat land rather than in the middle and upper parts (Table 2).…”
Section: In-situ Rain Water Harvestingmentioning
confidence: 99%